Conditional reprogramming culture conditions facilitate growth of lower-grade glioma models. Issue 5 (1st December 2020) - Yuan, Ming; White, David; Resar, Linda; Bar, Eli; Groves, Mari; Cohen, Alan; Jackson, Eric; Bynum, Jennifer; Rubens, Jeffrey; Mumm, Jeff; Chen, Liam; Jiang, Liqun; et al.
Abstract: Background: The conditional reprogramming cell culture method was developed to facilitate growth of senescence-prone normal and neoplastic epithelial cells, and involves co-culture with irradiated fibroblasts and the addition of a small molecule Rho kinase (ROCK) inhibitor. The aim of this study was to determine whether this approach would facilitate the culture of compact low-grade gliomas. Methods: We attempted to culture 4 pilocytic astrocytomas, 2 gangliogliomas, 2 myxopapillary ependymomas, 2 anaplastic gliomas, 2 difficult-to-classify low-grade neuroepithelial tumors, a desmoplastic infantile ganglioglioma, and an anaplastic pleomorphic xanthoastrocytoma using a modified conditional reprogramming cell culture approach. Results: Conditional reprogramming resulted in robust increases in growth for a majority of these tumors, with fibroblast conditioned media and ROCK inhibition both required. Switching cultures to standard serum containing media, or serum-free neurosphere conditions, with or without ROCK inhibition, resulted in decreased proliferation and induction of senescence markers. Rho kinase inhibition and conditioned media both promoted Akt and Erk1/2 activation. Several cultures, including one derived from a NF1-associated pilocytic astrocytoma (JHH-NF1-PA1) and one from a BRAF p.V600E mutant anaplastic pleomorphic xanthoastrocytoma (JHH-PXA1), exhibited growth sufficient for preclinical testing in vitro. In addition, JHH-NF1-PA1 cells survived and migrated in larval zebrafish orthotopic xenografts, while JHH-PXA1 formed orthotopic xenografts in mice histopathologically similar to the tumor from which it was derived. Conclusions: These studies highlight the potential for the conditional reprogramming cell culture method to promote the growth of glial and glioneuronal tumors in vitro, in some cases enabling the establishment of long-term culture and in vivo models.